Aortic valve-related aortopathy: assessing optimal timing of surgical intervention. (3rd October 2019) - Petersen, Johannes; Sequeira-Gross, Tatiana; Naito, Shiho; Reichenspurner, Hermann; Girdauskas, Evaldas
ABSTRACT: Introduction : Dilatation of the proximal aorta is often associated with an aortic valve disease (e.g. bicuspid aortic valve, aortic stenosis), so-called 'valve-related aortopathy.' The definition of optimal timing for surgical intervention in valve-related aortopathy remains incompletely clarified. The limited value of traditional diameter-based intervention criteria has been recognized and more sophisticated diagnostic tools are necessary. Areas covered : This article aims to give an overview on the most recent literature addressing the different forms of valve-related aortopathies and the optimal timing of surgical intervention. It highlights the valve morphotype-dependent (BAV vs TAV) and the valve lesion-dependent aortopathies (stenosis vs regurgitation) and outlines the current treatment options of those pathologies. Further, this review discusses novel serological and rheological markers, potentially helping in the decision-making process in valve-related aortopathy. Systematic literature searches were performed using PubMed and Embase up to July 2019. Expert opinion : The combination of serological biomarkers and quantitative rheological markers for transvalvular flow eccentricity might be an additional useful tool. A possible solution for the future could be a risk score which considers body-surface-adjusted aortic diameters, activity of certain circulating biomarkers, transvalvular flow patterns, possible connective tissue disorders, and the valve morphology to define an individualized treatment strategy.